The Role of International Trade and Investment in Poverty Reduction in Uzbekistan - Ashurova, Sitora (Journal of Regional Economics and Development, 2025)
This study analyzes the influence of international trade and foreign direct investment (FDI) on poverty reduction in Uzbekistan within the framework of the country’s economic reforms and global integration efforts. Using a qualitative analytical method supported by secondary data from the World Bank, IMF, ADB, and national statistics, the research explores how trade liberalization, export diversification, and foreign investment have contributed to improving income levels, employment, and access to basic services. The findings demonstrate that strategic FDI inflows and trade expansion since 2017 have played a pivotal role in reducing both monetary and multidimensional poverty, particularly through job creation and industrial diversification. However, challenges such as regional inequality, overreliance on energy exports, and institutional constraints persist. The study concludes that the sustainable reduction of poverty in Uzbekistan requires continued structural reforms, targeted social protection, and policies ensuring equitable regional development and environmental sustainability.